Kajian Minat Wisatawan Di Museum Memorial Jenderal Besar HM. Soeharto Di Kabupaten Bantul - Aji Wicaksosno (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2019)
Abstract - This study aimed to examine the interest of tourists at the HM General Memorial Museum. Suharto in Bantul Regency. This study employed descriptive qualitativemethodand the data were collected through interview, observation, literature studies, and documentation. Interview wascarried outwith managers and visitors (public peopleand students). The data analyzed using Miles Hubberman's qualitative descriptive analysis coveringdata reduction, data presentation, and drawing conclusion . The results showed that the interest of tourists at the HM General Memorial Museum Soeharto was quite high. In addition to that,the interest of the vast majority ofthe students who visited the HM General Memorial Museum. Soeharto was to conduct a study tour and find out the life history of the Great General HM. Suharto, while the personal interest of the university studentswas to find out information about the life history of the Great General HM. Suharto and gather with fellow students to just discuss and enjoy wifi facilities. The interest of the public peoplewasto reminisceaboutthe late Great General HM. Suharto. Visitors werealso interested coming to the HM General Memorial Museum. Suharto for recreation and gathering with friends and family.Moreover, they enjoyed adequate facilities available, of museum’s collections which were diverse and packaged in a modern way, as well as the historical elements related to Soeharto's life that invited visitors to be curious while providing education for visitors. Visitors also showed social interest when they visited to the HM General Memorial Museum. Soeharto either gathering with family and friends or participating in various community activities such as commemorating national holidays and participating in competitions, gymnastics and others. Keywords: Soeharto museum, tourism, tourist interest Abstract - Penelitian ini bertujuan untuk mengkaji minat wisatawan di Museum Memorial Jenderal Besar HM. Soeharto di Kabupaten Bantul. Metode dalam penelitian ini yaitu deskriptif kualitatif dengan pengumpulan data melalui wawancara, observasi, studi pustaka, dan dokumentasi. Wawancara dilakukan kepada pengelola dan pengunjung (umum, pelajar, dan mahasiswa). Analisis data menggunakan analisis deskriptif kualitatif Miles Hubberman yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa minat wisatawan di Museum Memorial Jenderal Besar HM. Soeharto cukup tinggi, Minat pribadi pelajar yang mengunjungi Museum Memorial Jenderal Besar HM. Soeharto umumnya adalah untuk melakukan study tour serta mengetahui sejarah kehidupan Jenderal Besar HM. Soeharto, sedangkan minat pribadi mahasiswa adalah untuk mengetahui informasi tentang sejarah kehidupan Jenderal Besar HM. Soeharto serta berkumpul dengan rekan-rekan sesama mahasiswa untuk berdiskusi maupun menikmati fasilitas wifi. Minat pribadi masyarakat umum adalah bernostalgia dengan mendiang Jenderal Besar HM. Soeharto. Pengunjung juga berminat datang ke Museum Memorial Jenderal Besar HM. Soeharto untuk berekreasi dan berkumpul bersama teman dan keluarga sambil memanfaatkan beragam fasilitas yang cukup memadai. Adanya koleksi museum yang beragam dan dikemas secara modern, serta adanya unsur historis terkait kehidupan Jenderal Besar HM. Soeharto yang mengundang rasa penasaran pengunjung sekaligus memberikan edukasi bagi pengunjung. Pengunjung juga menunjukkan minat sosial ketika datang ke Museum Memorial Jenderal Besar HM. Soeharto baik sekedar berkumpul dengan keluarga dan teman maupun mengikuti berbagai kegiatan komunitas seperti memperingati hari besar nasional maupun mengikuti kegiatan lomba, senam dan lain-lain. Kata kunci: museum soeharto, pariwisata, minat wisatawan